PENGARUH RASIO KINERJA KEUANGAN TERHADAP TINGKAT BAGI HASIL TABUNGAN MUDHARABAH (Pada Bank Umum Syariah yang listing di Bank Indonesia Periode 2010-2014) - Oetari Andari Prakoso; Amries Rusli Tanjung; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The aim of this study was to examine the Influence of CAR, ROA, ROE, NPF and BOPO On Profit Sharing of Mudharabah Savings on IslamicBank listing in BI period 2010-2014. The population in this study are all Islamic Banks in Indonesia are still in operation during the years 2010-2014 a total of 11 companies. Based on specified criteria, the company earned 11 Islamic Banks were used as samples in this study. This study uses secondary data in the form of publication of financial statements. Methods of data analysis using multiple linear regression analysis. Based on the analysis, the conclusions of this research are: 1) there is no significant effect Capital Adequacy Ratio on Profit Sharing of Mudharabah Savings in Islamic Banks with signifance value 0,163 > 0,05. 2) There is no significant effect return on assets on Profit Sharing of Mudharabah Savings in Islamic Banks with signifance value 0,070 > 0,05. 3) There is a significant effect Return On Equity on Profit Sharing of Mudharabah Savings in Islamic Banks with signifance value 0,040 < 0,05. 4) There is a significant influence NPF on Profit Sharing of Mudharabah Savings in Islamic Banks with signifance value 0,037 < 0,05. 5) There is a significant effect BOPO on Profit Sharing of Mudharabah Savings in Islamic Banks with signifance value 0,002 < 0,05. Based on the results of research on simultaneous test it was concluded that there was an effect of CAR, ROA, ROE, NPF, and BOPO together towards Profit Sharing of Mudharabah Savings in Islamic Banks.Keywords: Performance, Financial, Savings, Mudharabah, and Listing